Sobre a formação de professores de matemática em Cuiabá - MT (1960-1980) - Both, Bruna Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This present research aims to compose a historic version about the formation of Mathematics professors, between the decades 1960 to 1980, in Cuiaba, Mato Grosso. To do this, we will seek to develop understandings about courses for teachers in this area, available in the region and period above mentioned, building relations with the current educational policies. As methodology adopted in order to meet our proposal, we made use of Oral History, through which we constitute narratives that along written and image sources, enabled us to compose our analysis, highlighting, as much as possible and/or necessary, convergences/divergences between them, in order to form our narrative for training of Mathematics professors in Cuiaba, formulated from different voices, sources and perspectives. Our research also aims to contribute to the larger project of Mapping of the Formation and Activities of Mathematics Professors in Brazil, from the group of Oral History and Mathematics Education, GHOEM, of which we are part

A presente investigação visa compor uma versão histórica a respeito da formação de professores de Matemática, entre as décadas de 1960 a 1980, em Cuiabá, Mato Grosso. Para isso buscaremos elaborar compreensões sobre cursos de formação para docentes dessa área, ofertados na região e período em questão, tecendo relações com as então vigentes políticas educacionais. Como metodologia adotada, para atender à nossa proposta, nos valemos da História Oral, por meio da qual constituímos narrativas que, juntamente com fontes escritas e imagéticas, nos permitiram compor nossa análise, destacando, sempre que possível e/ou necessário, convergências/divergências entre elas, de modo a constituir nossa narrativa para a formação de professores de Matemática em Cuiabá, formulada a partir de diferentes vozes, fontes e perspectivas. Nossa pesquisa almeja também contribuir para o projeto maior de Mapeamento da formação e atuação dos professores de Matemática no Brasil, do Grupo de História Oral e Educação Matemática, GHOEM, do qual fazemos parte
Keywords: Universidade Federal de Mato Grosso; Teachers, Training of; Professores - Formação; Professores de matematica; Historia oral; Matemática - História - 1960-1980; Matemática - Estudo e ensino; Cuiaba (MT)